2018
DOI: 10.1530/eje-17-0707
|View full text |Cite
|
Sign up to set email alerts
|

Excess morbidity and mortality in patients with craniopharyngioma: a hospital-based retrospective cohort study

Abstract: Patients with craniopharyngioma are at an increased risk for T2DM, cerebral infarction, total mortality and mortality due to circulatory and respiratory diseases. Female sex, childhood-onset craniopharyngioma, hydrocephalus and tumour recurrence are important risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 36 publications
1
52
0
2
Order By: Relevance
“…Many published reports on long-term follow-up after childhood-onset CP are focused on survival rates and lack information on specific sequelae (22,25,26,27,30). However, QoS is frequently impaired in the pediatric age group due to treatment and/or disease-associated factors such as HI, neuropsychological (31,32) and neuroendocrine deficits (16,21,33,34,35,36,37,38,39,40,41,42) including GH deficiency being the most frequent pituitary deficiency (54-100%) (1,37,39). Our study is the first report in the literature, which analyzed not only long-term survival but also psychosocial status and QoS with special regard to timing and duration of GH substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many published reports on long-term follow-up after childhood-onset CP are focused on survival rates and lack information on specific sequelae (22,25,26,27,30). However, QoS is frequently impaired in the pediatric age group due to treatment and/or disease-associated factors such as HI, neuropsychological (31,32) and neuroendocrine deficits (16,21,33,34,35,36,37,38,39,40,41,42) including GH deficiency being the most frequent pituitary deficiency (54-100%) (1,37,39). Our study is the first report in the literature, which analyzed not only long-term survival but also psychosocial status and QoS with special regard to timing and duration of GH substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
“…HI and/or treatmentrelated hypothalamic lesions are major risk factors for the development of hypothalamic syndrome (16,51,52). Especially long-term CP survivors with hypothalamic lesions present with morbidity including severe obesity and impaired QoS (15,36,37,38,39,40,41,49,53). Previous follow-up studies reported on the prevalence of hypothalamic obesity but did not include detailed analyses of weight development during long-term follow-up (25,28,54).…”
Section: Discussionmentioning
confidence: 99%
“…The observation in some studies of increased mortality in female CP patients compared to males suggests some effect of gonadotrophin deficiency, and inappropriate or inadequate sex steroid replacement as contributing factors to mortality in CP . A study of adult CP patients who had undergone surgery for CP at a mean age of 12 years revealed lower bone mineral density in female CP patients, but not males, compared to controls; the authors speculated that insufficient oestrogen replacement after delayed puberty may have been implicated in their low bone density …”
Section: Anterior Pituitary Dysfunctionmentioning
confidence: 99%
“…Craniopharyngiomas (CP) are tumours of the pituitary sella and suprasellar region that are derived from embryonic remnants of Rathke's pouch with an incidence of only 0.13 per 100 000 patient years . CP is classified as a histologically benign tumour; however, a diagnosis of CP is associated with increased morbidity and mortality compared to both the background age‐ and sex‐matched population and to other conditions associated with hypopituitarism; therefore, the diagnosis cannot be considered to follow a benign course. CP patients suffer from high rates of pituitary hormone deficiencies, appetite and thirst disorders, sleep disorders and impaired temperature regulation …”
Section: Introductionmentioning
confidence: 99%
“…Some authors found higher mortality rates among females (24), whereas others did not observe any gender differences in terms of survival (28). Late mortality rates are associated with tumor and/ or treatment-related risk factors such as cerebrovascular disease, progressive disease with multiple recurrences, chronic neuroendocrine deficiencies (26,27,30,31,32,33) and non-alcoholic fatty liver disease (NAFLD) leading to liver cirrhosis (26,27,34,35,36). The standardized overall mortality rate varied from 2.88 to 9.28 in cohort studies performed by Erfurth et al The authors report that CP patients have a 3 to 19-fold increased cardiovascular mortality rate when compared with the general population.…”
Section: Survival and Late Morbiditymentioning
confidence: 99%